The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jcpt.13629
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunosuppressants improve pregnancy outcomes in women with idiopathic recurrent miscarriage: A meta‐analysis

Abstract: What is known and objective: Reports said immunotherapy is effective for the treatment of idiopathic recurrent miscarriage (RM). Immunotherapy is invasive, and lymphocyte therapy carries some risk of infection. Oral immunosuppressants have the advantages of simple administration and convenience; however, there is no statistical analysis of whether they can improve pregnancy outcomes in patients with idiopathic RM.Methods: Six databases were searched for studies on oral immunosuppressants and RM; 374 articles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…As an effective immunosuppressant, CsA is broadly employed in organ transplantation. 78 Now, CsA is also extensively utilized in various pregnancy complications, such as idiopathic or recurrent spontaneous abortion, 79 , 80 repeated implantation failure 81 , 82 and preeclampsia. 83 This therapeutic effect is supposed to be attributed to its widespread modulatory effects on various immunocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As an effective immunosuppressant, CsA is broadly employed in organ transplantation. 78 Now, CsA is also extensively utilized in various pregnancy complications, such as idiopathic or recurrent spontaneous abortion, 79 , 80 repeated implantation failure 81 , 82 and preeclampsia. 83 This therapeutic effect is supposed to be attributed to its widespread modulatory effects on various immunocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Rate of miscarriage was decreased post-treatment. However, the study reported significant heterogeneity and a moderate-to-severe risk of bias [209].…”
Section: Cyclosporinementioning
confidence: 91%
“…Steroid treatment was shown to improve live-birth outcomes in patients with RPL in a recent meta-analysis. 104 However, the studies included were inadequately powered, had co-intervention with heparin and aspirin, and had notable heterogeneity in inclusion criteria. 104 It is unclear whether prednisone improves outcomes for patients with RPL.…”
Section: Hematologicmentioning
confidence: 99%
“…104 However, the studies included were inadequately powered, had co-intervention with heparin and aspirin, and had notable heterogeneity in inclusion criteria. 104 It is unclear whether prednisone improves outcomes for patients with RPL. 105 Furthermore, its use is associated with an increased risk of prematurity, gestational diabetes mellitus, and hypertension.…”
Section: Hematologicmentioning
confidence: 99%